Optical and Electrical Properties of OPEFB Alkali Cellulose and PVA Composite - Adiati, Rima Fitria; Nikmatin, Siti; Irmansyah; Putri, Nazwa Nuradilla; Anandiwa, Siti Altirana (Green Engineering Society, 2024)
The Oil Palm Empty Fruit Bunch (OPEFB) is a byproduct of oil palm plantation and abundantly available in Indonesia. It is necessary to process the biomass waste into a more useful and higher value substances, such as semiconductor. This research aims to extract alpha-cellulose from OPEFB and process it into alkali cellulose - Polyvinyl Alcohol (PVA) composite for potential photodetector application. PVA acts as mechanical binding agent with 5%, 7.5%, and 10% concentration. Spectroscopy-based measurement is used to characterize the composite’s optical properties, while LCR meter is used to measure the electrical properties such as conductivity and capacitance. Using UV-Vis spectroscopy with wavelength range of 400-900 nm, it is observed that alkali cellulose with 5% PVA has the highest optical absorbance. Using Kubelka-Munk equation and Tauc plot, the energy gap of the composite was calculated, with the lowest energy gap is 2,769 eV at 5% PVA. Using LCR meter between frequency of 5 Hz to 5 MHz, one can measure conductivity (specific conductance) of a material, where highest obtained electrical conductivity is 2,65×1004 S/cm, which satisfy typical value of semiconductor characteristic. Measurement of Impedance also shows that composite with 7.5% PVA has the highest impedance at lower frequencies, then decreases to almost zero at frequency higher than 5000 Hz. These results demonstrate the potential of alkali cellulose-PVA composite as semiconductor sensors. These findings suggest the potential for developing low-cost, sustainable electronic devices.